Mediation as an Alternative for Resolving Family Conflicts in the View of Progressive Law and Islamic Law - Zulkarnaini Umar; Miftakhul Mukharrom; Achmad Sutiyono (International Conference On Law And Social Sciences, 2024)
Islamic law is law that originates from Islamic teachings with the main principle being mercy and spreading peace throughout the universe. This principle then makes Islamic law always capable of being a mediator and solution to all legal problems. Progressive law is a legal theory that starts from the assumption that law is for humans, not the other way around, so that progressive law does not accept the concept of law as an absolute and final institution but is determined by its ability to serve humans. Law is defined as an institution that aims to lead humans to a just, prosperous life and make humans happy. In the family environment, family law is defined as the law that regulates legal relationships arising from familial relationships, namely: marriage and relationships in the field of property law between husband and wife, relationships between parents and children, guardianship and curate . This research is library research , namely research in which the object is discovered by exploring library information, especially in the form of texts, such as books, encyclopedias, scientific journals, newspapers, magazines and other documents related to "mediation" . From this research it can be concluded that, mediation in the Islamic view is an effort to bring about peace which has become known as "Ishlah" between disputing parties by appointing a mediator, both in the realm of family law and others. while progressive law is legal thinking that prioritizes win-win solutions in resolving various problems, including resolving family conflicts and so on. Therefore , both Islamic law and progressive law view that mediation is a very strategic and positive step in creating polarization so that problems can be resolved quickly and without involving litigation, thus the law will be more humane.